Peranan Bappeda Dalam Pengentasan Kemiskinan Ekstrem Di Kabupaten Simeulue - zulkifli; Putri, Cut Mega (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to identify and examine the role of local governments in alleviating extreme poverty zones in the Simeulue Regency. The theory used in this study is the role of government according, which has four-dimensional variables, including entrepreneurship. Facilities, stimulus, and coordinator. This study uses a qualitative descriptive method with data collection obtained through three triangulation, including interviews, observations, and documentation studies. The data is analyzed through the concept, which includes reduction, showing that the role of the Simeulue District government in alleviating extreme poverty, which is reviewed through four dimensions, is not optimal, where from the variable, the role of the entrepreneur is still minimal work for the indigenous people of Simeulue. Then the last variable of the role of the stimulus of the local government of Simeulue people in extreme poverty zones can make the extremely poor of Simeulue develop more advanced, such as communication training and entrepreneurship.